2013
DOI: 10.1002/pbc.24483
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of pediatric plasmacytoid dendritic cell tumors with a contemporary regimen for acute lymphoblastic leukemia

Abstract: Dendritic cell leukemia (DCL) or hematodermic tumor is an uncommon subtype of acute leukemia. In contrast to adult cases, children tend to have a less aggressive course. The diagnosis of DCL should be considered when its characteristic morphologic features are present and leukemic cells co-express CD4 and CD56. Cases of DCL among pediatric patients have been reported to respond to therapeutic regimens for acute lymphoblastic leukemia, but details regarding the specifics of therapy are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…However, among commercial anti-CD22 antibody clones, only s-HCL-1 appears to be capable of recognizing an epitope expressed on pDCs and BPDCN. Expression of CD22 was also reported in cases of pediatric BPDCN [19]. One of two cases assessed in our study was positive for CD22 using the s-HCL-1 clone.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, among commercial anti-CD22 antibody clones, only s-HCL-1 appears to be capable of recognizing an epitope expressed on pDCs and BPDCN. Expression of CD22 was also reported in cases of pediatric BPDCN [19]. One of two cases assessed in our study was positive for CD22 using the s-HCL-1 clone.…”
Section: Discussionsupporting
confidence: 77%
“…particularly robust and deliver intense staining reactions, a useful feature in assessing residual disease. As reported by others, other antigens expressed in variable subsets of BPDCN include CD2, CD5, CD7, CD33, and CD117 [17][18][19]. Reineks et al have identified CD22 expression in normal pDCs and in four cases of BPDCN [20].…”
Section: Discussionmentioning
confidence: 80%
“…These lesions vary from hematoma-like macules to purplish plaques or nodules; focal lesions often affect the head and lower extremities, although they may spread throughout the body [ 11 , 12 ]. As shown in Figure 1 , the characteristic lesions of the cutaneous involvement are non-specific and are easily confused with other differential diagnoses [ 3 , 4 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from a subset of precursor cells called plasmacytoid dendritic cells or type II dendritic cells, characterized by the expression of CD123, CD4, and CD56 in the absence of markers of other lineages [1,2]. Although the disease predominantly affects older adults, with a median age of 65 years, it has been reported in other age groups, including infants and children [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…BPDCN typically affects elderly patients; however, it can be present at any age [ 3 ]. Pediatric patients are exceedingly rare with an unclear clinical course [ 3 , 4 ]. Currently, no standardized therapeutic approach has been established, although an acute lymphoblastic leukemia (ALL) type of treatment appears to be more effective in those patients who are able to tolerate aggressive chemotherapy [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%